Adult astrogenesis and functional astrocyte heterogeneity in the adult mouse hippocampus - Beckervordersandforth, Ruth (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Astrocytes in the adult dentate gyrus—balance between adult and developmental tasks - Chalmers, Nicholas; Masouti, Evangelia; Beckervordersandforth, Ruth (Molecular Psychiatry, 2024)
Astrocytes, a major glial cell type in the brain, are indispensable for the integration, maintenance and survival of neurons during development and adulthood. Both life phases make specific demands on the molecular and physiological properties of astrocytes, and most research projects traditionally focus on either developmental or adult astrocyte functions. In most brain regions, the generation of brain cells and the establishment of neural circuits ends with postnatal development. However, few neurogenic niches exist in the adult brain in which new neurons and glial cells are produced lifelong, and the integration of new cells into functional circuits represent a very special form of plasticity. Consequently, in the neurogenic niche, the astrocytes must be equipped to execute both mature and developmental tasks in order to integrate newborn neurons into the circuit and yet maintain overall homeostasis without affecting the preexisting neurons. In this review, we focus on astrocytes of the hippocampal dentate gyrus (DG), and discuss specific features of the astrocytic compartment that may allow the execution of both tasks. Firstly, astrocytes of the adult DG are molecularly, morphologically and functionally diverse, and the distinct astrocytes subtypes are characterized by their localization to DG layers. This spatial separation may lead to a functional specification of astrocytes subtypes according to the neuronal structures they are embedded in, hence a division of labor. Secondly, the astrocytic compartment is not static, but steadily increasing in numbers due to lifelong astrogenesis. Interestingly, astrogenesis can adapt to environmental and behavioral stimuli, revealing an unexpected astrocyte dynamic that allows the niche to adopt to changing demands. The diversity and dynamic of astrocytes in the adult DG implicate a vital contribution to hippocampal plasticity and represent an interesting model to uncover mechanisms how astrocytes simultaneously fulfill developmental and adult tasks.
CRIS-Team Scopus Importer:2024-01-12

Astrogenesis and dynamic of astrocytes in the adult mouse hippocampus - Schneider, Julia; Karpf, J.; Beckervordersandforth, Ruth (GLIA, 2019)
CRIS-Team WoS Importer:2020-01-10

Astrogenesis in the murine dentate gyrus is a life-long and dynamic process - Schneider, Julia; Weigel, Johannes; Wittmann, Marie-Theres; Svehla, Pavel; Ehrt, Sebastian; Zheng, Fang; Elmzzahi, Tarek; Karpf, Julian; Paniagua-Herranz, Lucia; Basak, Onur; Ekici, Arif Bülent; Wiesmann da Silva Reis, André; et al. (EMBO Journal, 2022)
Astrocytes are highly abundant in the mammalian brain, and their functions are of vital importance for all aspects of development, adaption, and aging of the central nervous system (CNS). Mounting evidence indicates the important contributions of astrocytes to a wide range of neuropathies. Still, our understanding of astrocyte development significantly lags behind that of other CNS cells. We here combine immunohistochemical approaches with genetic fate-mapping, behavioral paradigms, single-cell transcriptomics, and in vivo two-photon imaging, to comprehensively assess the generation and the proliferation of astrocytes in the dentate gyrus (DG) across the life span of a mouse. Astrogenesis in the DG is initiated by radial glia-like neural stem cells giving rise to locally dividing astrocytes that enlarge the astrocyte compartment in an outside-in-pattern. Also in the adult DG, the vast majority of astrogenesis is mediated through the proliferation of local astrocytes. Interestingly, locally dividing astrocytes were able to adapt their proliferation to environmental and behavioral stimuli revealing an unexpected plasticity. Our study establishes astrocytes as enduring plastic elements in DG circuits, implicating a vital contribution of astrocyte dynamics to hippocampal plasticity.
CRIS-Team WoS Importer:2022-04-29

Dentate gyrus astrocytes exhibit layer-specific molecular, morphological and physiological features - Karpf, Julian; Unichenko, Petr; Chalmers, Nicholas; Beyer, Felix; Wittmann, Marie-Theres; Schneider, Julia; Fidan, Elif; Reis, André; Beckervordersandforth, Jan; Brandner, Sebastian; Liebner, Stefan; Falk, Sven; et al. (Nature Neuroscience, 2022)
Neuronal heterogeneity has been established as a pillar of higher central nervous system function, but glial heterogeneity and its implications for neural circuit function are poorly understood. Here we show that the adult mouse dentate gyrus (DG) of the hippocampus is populated by molecularly distinct astrocyte subtypes that are associated with distinct DG layers. Astrocytes localized to different DG compartments also exhibit subtype-specific morphologies. Physiologically, astrocytes in upper DG layers form large syncytia, while those in lower DG compartments form smaller networks. Astrocyte subtypes differentially express glutamate transporters, which is associated with different amplitudes of glutamate transporter-mediated currents. Key molecular and morphological features of astrocyte diversity in the mice DG are conserved in humans. This adds another layer of complexity to our understanding of brain network composition and function, which will be crucial for further studies on astrocytes in health and disease.
CRIS-Team Scopus Importer:2022-12-09

Distinct forebrain regions define a dichotomous astrocytic profile in multiple system atrophy - Schneider, Yanni; Gauer, Carina; Andert, Marie; Hoffmann, Alana; Riemenschneider, M. J.; Krebs, W.; Chalmers, Nicholas; Lötzsch, C.; Naumann, Ulrike; Xiang, Wei; Rothhammer, Veit; Beckervordersandforth, Ruth; et al. (Acta Neuropathologica Communications, 2024)
The growing recognition of a dichotomous role of astrocytes in neurodegenerative processes has heightened the need for unraveling distinct astrocytic subtypes in neurological disorders. In multiple system atrophy (MSA), a rare, rapidly progressing atypical Parkinsonian disease characterized by increased astrocyte reactivity. However the specific contribution of astrocyte subtypes to neuropathology remains elusive. Hence, we first set out to profile glial fibrillary acidic protein levels in astrocytes across the human post mortem motor cortex, putamen, and substantia nigra of MSA patients and observed an overall profound astrocytic response. Matching the post mortem human findings, a similar astrocytic phenotype was present in a transgenic MSA mouse model. Notably, MSA mice exhibited a decreased expression of the glutamate transporter 1 and glutamate aspartate transporter in the basal ganglia, but not the motor cortex. We developed an optimized astrocyte isolation protocol based on magnetic-activated cell sorting via ATPase Na+/K+ transporting subunit beta 2 and profiled the transcriptomic landscape of striatal and cortical astrocytes in transgenic MSA mice. The gene expression profile of astrocytes in the motor cortex displayed an anti-inflammatory signature with increased oligodendroglial and pro-myelinogenic expression pattern. In contrast, striatal astrocytes were defined by elevated pro-inflammatory transcripts accompanied by dysregulated genes involved in homeostatic functions for lipid and calcium metabolism. These findings provide new insights into a region-dependent, dichotomous astrocytic response—potentially beneficial in the cortex and harmful in the striatum—in MSA suggesting a differential role of astrocytes in MSA-related neurodegenerative processes.
CRIS-Team Scopus Importer:2024-01-12

Distribution of Aldh1L1-CreERT2 Recombination in Astrocytes Versus Neural Stem Cells in the Neurogenic Niches of the Adult Mouse Brain - Beyer, Felix; Lüdje, Wichard; Karpf, Julian; Saher, Gesine; Beckervordersandforth, Ruth (Frontiers in Neuroscience, 2021)
In the adult central nervous system, neural stem cells (NSCs) reside in two discrete niches: the subependymal zone (SEZ) of the lateral ventricle and the subgranular zone (SGZ) of the dentate gyrus (DG). Here, NSCs represent a population of highly specialized astrocytes that are able to proliferate and give rise to neuronal and glial progeny. This process, termed adult neurogenesis, is extrinsically regulated by other niche cells such as non-stem cell astrocytes. Studying these non-stem cell niche astrocytes and their role during adult neuro- and gliogenesis has been hampered by the lack of genetic tools to discriminate between transcriptionally similar NSCs and niche astrocytes. Recently, Aldh1L1 has been shown to be a pan-astrocyte marker and that its promoter can be used to specifically target astrocytes using the Cre-loxP system. In this study we explored whether the recently described Aldh1L1-CreERT2 mouse line (Winchenbach et al., 2016) can serve to specifically target niche astrocytes without inducing recombination in NSCs in adult neurogenic niches. Using short- and long-term tamoxifen protocols we revealed high recombination efficiency and specificity in non-stem cell astrocytes and little to no recombination in NSCs of the adult DG. However, in the SEZ we observed recombination in ependymal cells, astrocytes, and NSCs, the latter giving rise to neuronal progeny of the rostral migratory stream and olfactory bulb. Thus, we recommend the here described Aldh1L1-CreERT2 mouse line for predominantly studying the functions of non-stem cell astrocytes in the DG under physiological and pathological conditions.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Aldh1L1; Aldh1L1-CreER; astrocytes; dentate gyrus; neural stem cells; neurogenic niche; subependymal zone

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

FoxO Function Is Essential for Maintenance of Autophagic Flux and Neuronal Morphogenesis in Adult Neurogenesis - Schäffner, Iris; Minakaki, Georgia; Khan, M. Amir; Balta, Elli-Anna; Schlötzer-Schrehardt, Ursula; Schwarz, Tobias J.; Beckervordersandforth, Ruth; Winner, Beate; Webb, Ashley E.; Depinho, Ronald A.; Paik, Jihye; Wurst, Wolfgang; et al. (Neuron, 2018)
Autophagy is a conserved catabolic pathway with emerging functions in mammalian neurodevelopment and human neurodevelopmental diseases. The mechanisms controlling autophagy in neuronal development are not fully understood. Here, we found that conditional deletion of the Forkhead Box O transcription factors FoxO1, FoxO3, and FoxO4 strongly impaired autophagic flux in developing neurons of the adult mouse hippocampus. Moreover, FoxO deficiency led to altered dendritic morphology, increased spine density, and aberrant spine positioning in adult-generated neurons. Strikingly, pharmacological induction of autophagy was sufficient to correct abnormal dendrite and spine development of FoxO-deficient neurons. Collectively, these findings reveal a novel link between FoxO transcription factors, autophagic flux, and maturation of developing neurons.
EVALuna2:34732

Heterogeneity of Radial Glia-Like Cells in the Adult Hippocampus - Gebara, Elias; Bonaguidi, Michael Anthony; Beckervordersandforth, Ruth; Sultan, Sebastien; Udry, Florian; Gijs, Pieter-Jan; Lie, Dieter Chichung; Ming, Guo-Li; Song, Hongjun; Toni, Nicolas (Stem Cells, 2016)
Adult neurogenesis is tightly regulated by the neurogenic niche. Cellular contacts between niche cells and neural stem cells are hypothesized to regulate stem cell proliferation or lineage choice. However, the structure of adult neural stem cells and the contact they form with niche cells are poorly described. Here, we characterized the morphology of radial glia-like (RGL) cells, their molecular identity, proliferative activity, and fate determination in the adult mouse hippocampus. We found the coexistence of two morphotypes of cells with prototypical morphological characteristics of RGL stem cells: Type ? cells, which represented 76% of all RGL cells, displayed a long primary process modestly branching into the molecular layer and type ? cells, which represented 24% of all RGL cells, with a shorter radial process highly branching into the outer granule cell layer-inner molecular layer border. Stem cell markers were expressed in type ? cells and coexpressed with astrocytic markers in type ? cells. Consistently, in vivo lineage tracing indicated that type ? cells can give rise to neurons, astrocytes, and type ? cells, whereas type ? cells do not proliferate. Our results reveal that the adult subgranular zone of the dentate gyrus harbors two functionally different RGL cells, which can be distinguished by simple morphological criteria, supporting a morphofunctional role of their thin cellular processes. Type ? cells may represent an intermediate state in the transformation of type ?, RGL stem cells, into astrocytes.
EVALuna2:26338

In vivo targeting of adult neural stem cells in the dentate gyrus by a split-cre approach - Beckervordersandforth, Ruth; Deshpande, Aditi; Schäffner, Iris; Huttner, Hagen; Lepier, Alexandra; Lie, Dieter Chichung; Goetz, Magdalena (Stem Cell Reports, 2014)
We describe the labeling of adult neural stem cells (aNSCs) in the mouse and human dentate gyrus (DG) by the combinatorial expression of glial fibrillary acidic protein (GFAP) and Prominin1, as revealed by immunohistochemistry. Split-Cre-based genetic fate mapping of these double-positive cells in the adult murine DG reveals their NSC identity, as they are self-renewing and contribute to neurogenesis over several months. Their progeny reacts to stimuli such as voluntary exercise with increased neurogenesis. Prominin1+/GFAP+ cells also exist in the adult human DG, the only region in the human brain for which adult neurogenesis has been consistently reported. Our data, together with previous evidence of such double-positive NSCs in the developing murine brain and in neurogenic regions of vertebrates with widespread neurogenesis, suggest that Prominin1- and GFAP-expressing cells are NSCs in a wide range of species in development and adulthood.
EVALuna2:22282

Lineage-reprogramming of pericyte-derived cells of the adult human brain into induced neurons - Karow, Marisa; Schichor, Christian; Beckervordersandforth, Ruth; Berninger, Benedikt (Journal of Visualized Experiments, 2014)
Direct lineage-reprogramming of non-neuronal cells into induced neurons (iNs) may provide insights into the molecular mechanisms underlying neurogenesis and enable new strategies for in vitro modeling or repairing the diseased brain. Identifying brain-resident non-neuronal cell types amenable to direct conversion into iNs might allow for launching such an approach in situ, i.e. within the damaged brain tissue. Here we describe a protocol developed in the attempt of identifying cells derived from the adult human brain that fulfill this premise. This protocol involves: (1) the culturing of human cells from the cerebral cortex obtained from adult human brain biopsies; (2) the in vitro expansion (approximately requiring 2-4 weeks) and characterization of the culture by immunocytochemistry and flow cytometry; (3) the enrichment by fluorescence-activated cell sorting (FACS) using anti-PDGF receptor-? and anti-CD146 antibodies; (4) the retrovirus-mediated transduction with the neurogenic transcription factors sox2 and ascl1; (5) and finally the characterization of the resultant pericyte-derived induced neurons (PdiNs) by immunocytochemistry (14 days to 8 weeks following retroviral transduction). At this stage, iNs can be probed for their electrical properties by patch-clamp recording. This protocol provides a highly reproducible procedure for the in vitro lineage conversion of brain-resident pericytes into functional human iNs.
EVALuna2:26324

Mitochondrial Dysfunction in Astrocytes Impairs the Generation of Reactive Astrocytes and Enhances Neuronal Cell Death in the Cortex Upon Photothrombotic Lesion - Fiebig, Christian; Keiner, Silke; Ebert, Birgit; Schäffner, Iris; Jagasia, Ravi; Lie, Dieter Chichung; Beckervordersandforth, Ruth (Frontiers in Molecular Neuroscience, 2019)
Mitochondria are key organelles in regulating the metabolic state of a cell. In the brain, mitochondrial oxidative metabolism is the prevailing mechanism for neurons to generate ATP. While it is firmly established that neuronal function is highly dependent on mitochondrial metabolism, it is less well-understood how astrocytes function rely on mitochondria. In this study, we investigate if astrocytes require a functional mitochondrial electron transport chain (ETC) and oxidative phosphorylation (oxPhos) under physiological and injury conditions. By immunohistochemistry we show that astrocytes expressed components of the ETC and oxPhos complexes in vivo. Genetic inhibition of mitochondrial transcription by conditional deletion of mitochondrial transcription factor A (Tfam) led to dysfunctional ETC and oxPhos activity, as indicated by aberrant mitochondrial swelling in astrocytes. Mitochondrial dysfunction did not impair survival of astrocytes, but caused a reactive gliosis in the cortex under physiological conditions. Photochemically initiated thrombosis induced ischemic stroke led to formation of hyperfused mitochondrial networks in reactive astrocytes of the perilesional area. Importantly, mitochondrial dysfunction significantly reduced the generation of new astrocytes and increased neuronal cell death in the perilesional area. These results indicate that astrocytes require a functional ETC and oxPhos machinery for proliferation and neuroprotection under injury conditions.
CRIS-Team WoS Importer:2019-03-06

NR2F1 shapes mitochondria in the mouse brain, providing new insights into Bosch-Boonstra-Schaaf optic atrophy syndrome. - Bonzano, Sara; Dallorto, Eleonora; Molineris, Ivan; Michelon, Filippo; Crisci, Isabella; Gambarotta, Giovanna; Neri, Francesco; Oliviero, Salvatore; Beckervordersandforth, Ruth; Lie, Dieter Chichung; Peretto, Paolo; Bovetti, Serena; et al. (Disease Models & Mechanisms, 2023)
The nuclear receptor NR2F1 acts as a strong transcriptional regulator in embryonic and postnatal neural cells. In humans, mutations in the NR2F1 gene cause Bosch-Boonstra-Schaaf optic atrophy syndrome (BBSOAS), a rare neurodevelopmental disorder characterized by multiple clinical features including vision impairment, intellectual disability and autistic traits. In this study, we identified, by genome-wide and in silico analyses, a set of nuclear-encoded mitochondrial genes as potential genomic targets under direct NR2F1 transcriptional control in neurons. By combining mouse genetic, neuroanatomical and imaging approaches, we demonstrated that conditional NR2F1 loss of function within the adult mouse hippocampal neurogenic niche results in a reduced mitochondrial mass associated with mitochondrial fragmentation and downregulation of key mitochondrial proteins in newborn neurons, the genesis, survival and functional integration of which are impaired. Importantly, we also found dysregulation of several nuclear-encoded mitochondrial genes and downregulation of key mitochondrial proteins in the brain of Nr2f1-heterozygous mice, a validated BBSOAS model. Our data point to an active role for NR2F1 in the mitochondrial gene expression regulatory network in neurons and support the involvement of mitochondrial dysfunction in BBSOAS pathogenesis.
EVALuna2:537078

Role of astrocytes in the neurogenic niches - Schneider, Julia; Karpf, Julian; Beckervordersandforth, Ruth (Astrocytes, 2019)
In the mammalian brain, highly specialized astrocytes serve as neural stem cells (NSCs) that divide and give rise to new neurons, in a process called neurogenesis. During embryonic development NSCs generate almost all neurons of the brain. Soon after birth the neurogenic potential of NSCs is highly reduced, and neurogenesis occurs only in two specialized brain regions called the neurogenic niches. Niche cells are essential to stem cells as they provide structural and nutritional support, and control fundamental stem cell decisions. Astrocytes, major components of the adult neurogenic niches, are evolving as important regulators of neurogenesis, by controlling NSC proliferation, fate choice, and differentiation of the progeny. Therefore, astrocytes contribute to neurogenesis in two ways: As NSCs and as niche cells. This review highlights the role of astrocyte-like NSCs during development and adulthood, and summarizes how niche astrocytes control the process of adult neurogenesis.
CRIS-Team Scopus Importer:2019-07-30
Keywords: Adult neurogenesis; Astrocytes; Neural stem cell niche; Neural stem cells

Role of Mitochondrial Metabolism in the Control of Early Lineage Progression and Aging Phenotypes in Adult Hippocampal Neurogenesis - Beckervordersandforth, Ruth; Ebert, Birgit; Schäffner, Iris; Moss, Jonathan; Fiebig, Christian; Shin, Jaehoon; Moore, Darcie L.; Ghosh, Laboni; Trinchero, Mariela F.; Stockburger, Carola; Friedland, Kristina; Steib, Kathrin; et al. (Neuron, 2017)
EVALuna2:4763

Sox9 regulates melanocytic fate decision of adult hair follicle stem cells - Stüfchen, Isabel; Beyer, Felix; Stäbler, Sebastian; Fischer, Stefan; Kappelmann, Melanie; Beckervordersandforth, Ruth; Boßerhoff, Anja Katrin (iScience, 2023)
The bulge of hair follicles harbors Nestin+ (neural crest like) stem cells, which exhibit the potential to generate various cell types including melanocytes. In this study, we aimed to determine the role of Sox9, an important regulator during neural crest development, in melanocytic differentiation of those adult Nestin+ cells. Immunohistochemical analysis after conditional Sox9 deletion in Nestin+ cells of adult mice revealed that Sox9 is crucial for melanocytic differentiation of these cells and that Sox9 acts as a fate determinant between melanocytic and glial fate. A deeper understanding of factors that regulate fate decision, proliferation and differentiation of these stem cells provides new aspects to melanoma research as melanoma cells share many similarities with neural crest cells. In summary, we here show the important role of Sox9 in melanocytic versus glial fate decision of Nestin+ stem cells in the skin of adult mice.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Cell biology; Developmental biology; Molecular biology

Synergic Functions of miRNAs Determine Neuronal Fate of Adult Neural Stem Cells - Pons-Espinal, Meritxell; De Luca, Emanuela; Marzi, Matteo Jacopo; Beckervordersandforth, Ruth; Armirotti, Andrea; Nicassio, Francesco; Fabel, Klaus; Kempermann, Gerd; Tonelli, Davide De Pietri (Stem Cell Reports, 2017)
Adult neurogenesis requires the precise control of neuronal versus astrocyte lineage determination in neural stem cells. While microRNAs (miRNAs) are critically involved in this step during development, their actions in adult hippocampal neural stem cells (aNSCs) has been unclear. As entry point to address that question we chose DICER, an endoribonuclease essential for miRNA biogenesis and other RNAi-related processes. By specific ablation of Dicer in aNSCs in vivo and in vitro, we demonstrate that miRNAs are required for the generation of new neurons, but not astrocytes, in the adult murine hippocampus. Moreover, we identify 11 miRNAs, of which 9 have not been previously characterized in neurogenesis, that determine neurogenic lineage fate choice of aNSCs at the expense of astrogliogenesis. Finally, we propose that the 11 miRNAs sustain adult hippocampal neurogenesis through synergistic modulation of 26 putative targets from different pathways.
EVALuna2:4761

Transcription-Factor-Dependent Control of Adult Hippocampal Neurogenesis - Beckervordersandforth, Ruth; Zhang, Chun-Li; Lie, Dieter Chichung (Cold Spring Harbor Perspectives in Biology, 2015)
Adult-generated dentate granule neurons have emerged as major contributors to hippocampal plasticity. New neurons are generated from neural stem cells through a complex sequence of proliferation, differentiation, and maturation steps. Development of the new neuron is dependent on the precise temporal activity of transcription factors, which coordinate the expression of stage-specific genetic programs. Here, we review current knowledge in transcription factor-mediated regulation of mammalian neural stem cells and neurogenesis and will discuss potential mechanisms of how transcription factor networks, on one hand, allow for precise execution of the developmental sequence and, on the other hand, allow for adaptation of the rate and timing of adult neurogenesis in response to complex stimuli. Understanding transcription factor-mediated control of neuronal development will provide new insights into the mechanisms underlying neurogenesis-dependent plasticity in health and disease.
EVALuna2:26328

Two novel CreERT2 transgenic mouse lines to study melanocytic cells in vivo - Stüfchen, Isabel; Beckervordersandforth, Ruth; Fischer, Stefan; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Beyer, Felix (Pigment Cell & Melanoma Research, 2022)
The skin of adult mammals protects from radiation, physical and chemical insults. While melanocytes and melanocyte-producing stem cells contribute to proper skin function in healthy organisms, dysfunction of these cells can lead to the generation of malignant melanoma—the deadliest type of skin cancer. Addressing cells of the melanocyte lineage in vivo represents a prerequisite for the understanding of melanoma on cellular level and the development of preventive and treatment strategies. Here, the inducible Cre-loxP-system has emerged as a promising tool to specifically target, monitor, and modulate cells in adult mice. Re-analysis of existing sequencing data sets of melanocytic cells revealed that genes with a known function in neural cells, including neural stem cells (Aldh1L1 and Nestin), are also expressed in melanocytic cells. Therefore, in this study, we explored whether the promoter activity of Nestin and Aldh1L1 can serve to target cells of the melanocyte lineage using the inducible CreERT2-loxP-system. Using an immunohistochemical approach and different time points of analysis, we were able to map the melanocytic fate of recombined stem cells in the adult hair follicle of Nestin-CreERT2 and Aldh1L1-CreERT2 transgenic mice. Thus, we here present two new mouse models and propose their use to study and putatively modulate adult melanocytic cells in vivo.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Aldh1L1-CreER; inducible Cre mouse line; melanocyte; melanocyte stem cell; multipotent stem cell; Nestin-CreER

Untangling human neurogenesis to understand and counteract brain disorders - Beckervordersandforth, Ruth; Rolando, Chiara (Current Opinion in Pharmacology, 2020)
Neurogenesis in the human postnatal brain occurs in two regions, the subventricular zone of the later ventricle and the dentate gyrus of the hippocampus. While it is well accepted that SVZ and hippocampal neurogenesis are active during juvenile stages in human, their contribution during adulthood and ageing as well as pathological states is recently animating the neural stem cell research field. In this review we will discuss recent evidence about the organization of SVZ and hippocampal neurogenic niches, and will report on how human adult neurogenesis may contribute to disease and appears to respond to neurodegeneration. In light of these novel findings, we will discuss how we can target human adult neurogenesis in order to influence brain disease trajectories.
CRIS-Team Scopus Importer:2020-01-07